The antioxidant protein Oxr1 influences aspects of mitochondrial morphology - Wu, Y; Davies, K; Oliver, P (Elsevier, 2016)
Oxidative stress (OS) and mitochondrial dysfunction are implicated in neurodegenerative disease, suggesting that antioxidant defense systems are critical for cell survival in the central nervous system (CNS). Oxidation resistance 1 (OXR1) can protect against OS in cellular and mouse models of amyotrophic lateral sclerosis (ALS) when over-expressed, whereas deletion of Oxr1 in mice causes neurodegeneration. OXR1 has emerged therefore as an essential antioxidant protein that controls the susceptibility of neurons to OS. It has been suggested that OXR1 is localised to mitochondria, yet the functional significance of this has not been investigated in the context of neuronal cell death. In order to characterise the role of Oxr1 in mitochondria, we investigated its sub-mitochondrial localisation and demonstrate that specific isoforms are associated with the outer mitochondrial membrane, while the full-length Oxr1 protein is predominately cytoplasmic. Interestingly, cytoplamsic over-expression of these mitochondrially-localised isoforms was still able to protect against OS-induced cell death and prevent rotenone-induced mitochondrial morphological changes. To study the consequences of Oxr1 deletion in vivo, we utilised the bella ataxic mouse mutant. We were unable to identify defects in mitochondrial metabolism in primary cerebellar granule cells (GCs) from bella mice, however a reduction in mitochondrial length was observed in mutant GCs compared to those from wild-type. Furthermore, screening a panel of proteins that regulate mitochondrial morphology in bella GCs revealed de-regulation of phospho-Drp1(Ser616), a key mitochondrial fission regulatory factor. Our data provide new insights into the function of Oxr1, revealing that specific isoforms of this novel antioxidant protein are associated with mitochondria and that the modulation of mitochondrial morphology may be an important feature of its protective function. These results have important implications for the potential use of OXR1 in future antioxidant therapies.